Molecular Characterization of Red Rice Germplasm Using SSR Markers - Gupta, Kavita; Sarawgi, A. K.; Babu, V. Ravindra (International Journal of Bio-resource and Stress Management, 2016)
Microsatellites are simple sequence repeats (SSR) of 1−6 nucleotides. Their potential for automation and their inheritance in a co-dominant manner are additional advantages when compared with other types of molecular markers. SSRs are highly polymorphic, genome specific, abundant and co-dominant, and have recently become important genetic markers in cereals including rice and wheat.In present study SSR markers was applied for molecular characterization of 32 genotypes including 30 red rice genotypes and 2 popular white pericarped varieties as checks.Molecular characterization showed considerable level of genetic diversity among the selected genotypes. All amplified products with primers had shown polymorphic and distinguishable banding patterns which indicate the genetic diversity of rice genotypes. A total of 124 reproducible and scorable polymorphic bands generated with 19 primers among the 32 genotypes. The similarity matrices were subjected to sequential agglomerative hierarchical nested (SHAN) clustering using UPGMA in NTSYS-pc version 1.70. Considerable amount of diversity is present between different genotypes of different clusters. This diversity is of great significance in new breeding programme. Genetic improvement mainly depends on the extent of genetic variability present in the population. The molecular marker is a useful tool for assessing genetic variations and resolving cultivar identities.